The potential energy of plastic solid waste as an alternative fuel for power plants in Indonesia - Anshar, Muhammad (2013)
Studies on the potential of plastic solid waste (PSW) as a fuel supplement for power plant was conducted to determine the potential energy and economic value in Indonesia. In analyzing the potential energy and economic value of PSW, 15 cities provinces having municipal solid waste production of greater than 1,000 tons/day were selected. The study showed that with the total potential of PSW of around 693 tons/day, the electrical energy potential available is around 7,987 MWh/day. The PSW equivalent with coal is approximately 1,065 tons/day, and its equivalent to the oil is around 593 tons/day. In conclusion, the PSW is an environmental pollution material but have the energy and economic potential to be used as a fuel supplement for the power plants. Thereby, it can save the use of coal by means co-combustion with PSW and at the same time be able overcome the environmental problems caused by pollution PSW in Indonesia.